Academically Inclined: Predictors of Early Career Trajectory and Avenues for Early Intervention Among Neurosurgery Trainees. Issue 4 (15th April 2023) - Hulou, M. Maher; Park, Marian T.; Essibayi, Muhammed Amir; McLouth, Christopher J.; Benner, Dimitri; Samaan, Christopher Ala; Madriñán-Navia, Humberto Jose; Howshar, Jacob T.; Graffeo, Christopher S.; Lawton, Michael T.
Abstract : BACKGROUND: The relationship of academic activities before and during neurosurgery residency with fellowship or career outcomes has not been studied completely. OBJECTIVE: To assess possible predictors of fellowship and career outcomes among neurosurgery residents. METHODS: US neurosurgery graduates (2018-2020) were assessed retrospectively for peer-reviewed citations of preresidency vs intraresidency publications, author order, and article type. Additional parameters included medical school, residency program, degree (MD vs DO; PhD), postgraduate fellowship, and academic employment. RESULTS: Of 547 neurosurgeons, 334 (61.1%) entered fellowships. Fellowship training was significantly associated with medical school rank and first-author publications. Individuals from medical schools ranked 1 to 50 were 1.6 times more likely to become postgraduate fellows than individuals from medical schools ranked 51 to 92 (odds ratio [OR], 1.63 [95% CI 1.04-2.56]; P = .03). Residents with ≥2 first-author publications were almost twice as likely to complete a fellowship as individuals with <2 first-author publications (OR, 1.91 [95% CI 1.21-3.03]; P = .006). Among 522 graduates with employment data available, academic employment obtained by 257 (49.2%) was significantly associated with fellowship training and all publication-specific variables. Fellowship-trained graduates were twice as likely to pursue academic careers (OR, 1.99 [95% CI 1.34-2.96]; P < .001) as were individuals with ≥3 first-author publications ( P < .001), ≥2 laboratory publications ( P = .04), or ≥9 clinical publications ( P < .001). CONCLUSION: Research productivity, medical school rank, and fellowships are independently associated with academic career outcomes of neurosurgeons. Academically inclined residents may benefit from early access to mentorship, sponsorship, and publishing opportunities.